Atrazina reduz a expressão de genes imunológicos em peixes - Kirsten, Karina Schreiner (2016)
Silver catfish (Rhamdia quelen) is ubiquitously distributed in South American rivers and lakes and adapts easily to intensive farming either alone or comingled to other fish species. In South Brazil, fish farming ponds are vicinal to agricultural areas where intensive agrichemical usage, mainly herbicides, supports crop production but ends up as water and soil contaminant. Fish exposure to atrazine-based herbicides might cause deleterious effect on several physiological and biochemical pathways including those related to the immune system. The functioning of immune system relies on cell-to-cell interactions that are mainly orchestrated by cytokines which, in turn, are major players of the immune response. In addition, enzymes produced by phagocytic cells, such as myeloperoxidase, are fundamental to get rid of invading microorganisms. In this scenario, the capability to evaluate the expression of immune system related genes is needed mainly to establish molecular pathways related to the alterations observed in the immune system of agrichemicals-exposed fish. Thus, in this study, our main goal was to evaluate the expression of selected immunological genes, by real time polymerase chain reaction (RT-qPCR), in fish exposed to atrazine. Primers for the immune related genes were designed by comparing the target genes from several fish species phylogenetically related to Rhamdia quelen. We selected primers for β-actin and 18s RNA gene, that were used as control genes, and for Tumor Necrosis Factor alfa (TNF-α), Interleukin 1 beta (IL-1β), IRAK4, myeloperoxidase and Mx genes. To evaluate gene expression in vivo, fish were equally distributed in three tanks, a control group without any chemical, and two additional tanks containing each 0,102 mg/L and 1,02 mg/L of atrazine that corresponded to 1% and 10% of the atrazine CL50-96h, respectively. Fish were captured 48h post-exposure to remove the cranial kidney from which mononuclear leukocytes were isolated and submitted to total RNA extraction. In vitro gene expression was evaluated in mononuclear leukocytes, isolated from three healthy fish, cultivated for 24h with media containing 1 and 10 µg/ml of atrazine. Leukocytes exposed only to the agrichemical solvent, cultivated under the same conditions, were used as controls. In the in vivo experiment, the expression of myeloperoxidase and IL-1β genes were significantly reduced (p<0.05) in fish exposed to 1,02 mg/L of atrazine but the expression of TNF-α was reduced in both atrazineexposed groups.The expressions of Mx and IRAK4 genes were not altered. In the in vitro experiment, however, the expression of mieloperoxidase and IRAK4 were significantly reduced (p<0.05) in leukocytes exposed to 10 µg/ml of atrazine and the expression of TNF-α was significantly reduced in cells exposed to 1 µg/ml of atrazine. The expression of IL-1β and Mx was not altered in the in vitro experiment. In general, the result obtained from the in vivo and in vitro experiments were similar. With this study we demonstrated that atrazine causes reduction in the expression of several genes fundamental to immune response regulation which, in turn, could possible explain the reduction of fish defense mechanisms toward challenging pathogens commonly found on the aquatic environment.